A study of ruxolitinib response–based stratified treatment for pediatric hemophagocytic lymphohistiocytosis - Zhang, Qing; Zhao, Yun-Ze; Ma, Hong-Hao; Wang, Dong; Cui, Lei; Li, Wei-Jing; Wei, Ang; Wang, Chan-Juan; Wang, Tian-You; Li, Zhi-Gang; Zhang, Rui (Blood, 2022)
Hemophagocytic lymphohistiocytosis (HLH) is a lethal disorder characterized by hyperinflammation. Recently, ruxolitinib (RUX), targeting key cytokines in HLH, has shown promise for HLH treatment. However, there is a lack of robust clinical trials evaluating its efficacy, especially its utility as a frontline therapy. In this study (www.chictr.org.cn, ChiCTR2000031702), we designed ruxolitinib as a first-line agent for pediatric HLH and stratified the treatment based on its early response. Fifty-two newly diagnosed patients were enrolled. The overall response rate (ORR) of ruxolitinib monotherapy (day 28) was 69.2% (36/52), with 42.3% (22/52) achieving sustained complete remission (CR). All responders achieved their first response to ruxolitinib within 3 days. The response to ruxolitinib was significantly associated with the underlying etiology at enrollment (P = .009). Epstein-Barr virus (EBV)-HLH patients were most sensitive to ruxolitinib, with an ORR of 87.5% (58.3% in CR). After ruxolitinib therapy, 57.7% (30/52) of the patients entered intensive therapy with additional chemotherapy. Among them, 53.3% (16/30) patients achieved CR, and 46.7% (14/30) patients dominated by chronic active EBV infection-associated HLH (CAEBV-HLH) developed refractory HLH by week 8. The median interval to additional treatment since the first ruxolitinib administration was 6 days (range, 3-25 days). Altogether, 73.1% (38/52) of the enrolled patients achieved CR after treatment overall. The 12-month overall survival (OS) for all patients was 86.4% (95% confidence interval [CI], 77.1% to 95.7%). Ruxolitinib had low toxicity and was well tolerated compared with intensive chemotherapy. Our study provides clinical evidence for ruxolitinib as a frontline agent for pediatric HLH. The efficacy was particularly exemplified with stratified regimens based on the early differential response to ruxolitinib. This study was registered in the Chinese Clinical Trials Registry Platform (http://www.chictr.org.cn/) as ChiCTR2000031702. •The ruxolitinib response–based stratified therapy achieved CR in 73.1% of HLH patients, with a 12-month survival of 86.4%.•Ruxolitinib, as a first-line agent, had a rapid efficacy for pediatric HLH and led to sustained CR in 42.3% of patients with good tolerance. [Display omitted]